Efeitos da poda radicular na produçáo de plantas de sobreiro em viveiro (quercus suber l.) - Santos, Maria de Lourdes; PAULINO, ISABEL MARGARIDA ORFÁO (II Congreso Forestal Español, 1997)
The work was accomplished in the Seed Laboratory of National Forestry Station. The aim is to observe, in the nursery plants production, the pruning root effects made at several levels. The seeds provenance are the selected trees. The results permitted to conclude that: • The plants submitted to a radicular pruning at 1/3 and 2/3 present a better thickening and become woody plants; • The plants submitted to a radicular pruning at 1/3 present higher size of aerial parts; • The plants submitted to a radicular pruning at 2/3 present higher rate of secondary roots. K.
Keywords: Nursery; Plants; Quercus suber; radicular pruning